Association of neonatal hyperbilirubinemia with cord albumin among term appropriate for gestational age neonates - Shah, Shweta K.; Jha, Anand K.; Sharma, Satish; Gupta, Sanjay (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal hyperbilirubinemia (NH) is the most common abnormality seen during the neonatal period. It affects nearly 60% of term and 80% of preterm neonates during the first week of life. Early discharge of healthy term and late preterm newborns after normal vaginal delivery is a common practice however there are reports of bilirubin induced brain damage (kernicterus) occurring in these infants. Therefore, to ascertain whether cord albumin can be used as a reliable indicator for predicting neonatal hyperbilirubinemia. Methods: A tertiary care hospital-based cross-sectional study was conducted in 142 healthy late preterm and term newborns of either gender with icterus appearing only after 24 hour of life with no other illness using a non-probability sampling method. Data analysis was done using statistical package for the social sciences (SPSS) version 16. Chi-square was used to determine the association between cord albumin and hyperbilirubinemia. Results: There is a significant negative correlation between cord albumin and serum bilirubin at 72-96 hours of life (p=0.001). A total of 142 healthy late preterm and term neonates included. The study group based on Cord serum albumin (CSA) levels ≤2.8 g/dl, 2.9-3.3 g/dl, and ≥3.4 g/dl shows 77.27%, 22.7% and none respectively developed NH requiring phototherapy. According to receiver operating curve (ROC) analysis, the cutoff point of 2.75 g/dl provides the best sensitivity and specificity result. Conclusions: Cord serum albumin level ≥3.4 g/dl are probably safe for early discharge whereas cord serum albumin level <3.4 g/dl will need a close follow-up to check for the development of jaundice.